2009
DOI: 10.1136/thx.2009.118620
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term efficacy of a community-based COPD management programme in less advanced COPD: a randomised controlled trial

Abstract: Background: The effectiveness of pulmonary rehabilitation in advanced COPD is well established, but few data are available in less advanced disease. Methods: In a 2 year randomised controlled trial, 199 patients with an average moderate airflow obstruction but impaired exercise capacity (mean (SD) forced expiratory volume in 1 s (FEV 1 ) 60 (16)%, peak work load (Wmax) ,70%) were randomised to the INTERdisciplinary COMmunity-based COPD management programme (INTERCOM) or usual care. Intervention consisted of 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
166
5
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(203 citation statements)
references
References 36 publications
8
166
5
24
Order By: Relevance
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Thirteen studies were done in Europe 17,19,21,31,33,38,42,43,45,46,48,49,50 , six in Asia 30,36,39,40,44,47 , two in Australasia 34,35 , one in North America 41 , and one in South America 32 . Among the studies included in the review, 19 17,18,19,30,31,32,33,34,36,38,39,40,42,43,44,46,47,48,49,50 compared HCPR to control group (n = total 893; n HCPR = 485), while four 35,37,41,45 compared HCPR to OPR (n total = 375; n HCPR = 178). No studies reported harmful effects related to HCPR during interventions.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Clinical trials have shown that inhaled bronchodilators and to a lesser extent corticosteroids improve symptoms and reduce exacerbations. 2,5,6 Notably, recent studies suggest that lung function decline is fastest in early instead of advanced COPD, and that maintenance treatment with inhaled medication is also beneficial in moderate, and not only in severe, obstruction.…”
mentioning
confidence: 99%